Analisis Sistem Informasi Layanan Antrian Online Pasien Rawat Jalan RSUD Haji Makassar - Momen Amalia (Asosiasi Riset Ilmu Kesehatan Indonesia, 2023)
Background: With the online queuing application at RSUD Haji Makassar, registration should be able to run effectively. However, the queuing system at the Makassar Haji Hospital is not working well or can be said to be ineffective because patients still choose to register offline compered to registering online via the Makassar Haji Hospital queuing application which has been provided by the hospital.Objective: To determine the factors that influence the effectiveness of the online queuing system for outpatiens at RSUD Haji Makassar. Method: The research used was quantitative research using cross-sectional methods. Data collections used aquestionnaire, the sample in study was 95 systems users (patiens) at RSUD Haji Makassar. Data analysis using the chi-square test, namely to see the relationship between the independent variable and the dependent variable. Research results: There is an influence of relative advantage (p=0.002), compability (p=0.000),complexity (p=0.000), possibility of trying (tryability) (p=0.000), ease observed (observability) (p=0.000), on the effectiveness of the online queuing system at RSUD Haji Makassar.Conclusion: The factors in all variables examined in this study show that there is an influence on the effectiveness of the online queuing system. It is hoped that RSUD Haji Makassar will hold outreach and education to increase the effectiveness of the online queue system